2010
DOI: 10.1073/pnas.1005978107
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis BRCA2 and RAD51 proteins are specifically involved in defense gene transcription during plant immune responses

Abstract: Systemic acquired resistance (SAR) is a plant immune response associated with both transcriptional reprogramming and increased homologous DNA recombination (HR). SNI1 is a negative regulator of SAR and HR, as indicated by the increased basal expression of defense genes and HR in sni1. We found that the sni1 phenotypes are rescued by mutations in BREAST CANCER 2 (BRCA2). In humans, BRCA2 is a mediator of RAD51 in pairing of homologous DNA. Mutations in BRCA2 cause predisposition to breast/ovarian cancers; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 30 publications
3
112
0
Order By: Relevance
“…Our CHIP assay showed that EMSY still binds to the promoter of IFN-stimulated genes in the absence of BRCA2, suggesting that the regulation of IFN-related genes by BRCA2 complex is independent of EMSY's chromatin binding capacity. CHIP result in Arabidopsis demonstrated that another BRCA2 interaction protein, RAD51, was recruited to the promoters of defence genes during plant immune response [8]. However, in our study, when RAD51 was over-expressed, it did not modulate IFN-α induced ISRE activity (in contrast with BRCA2 expression) ( Figure 5b).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our CHIP assay showed that EMSY still binds to the promoter of IFN-stimulated genes in the absence of BRCA2, suggesting that the regulation of IFN-related genes by BRCA2 complex is independent of EMSY's chromatin binding capacity. CHIP result in Arabidopsis demonstrated that another BRCA2 interaction protein, RAD51, was recruited to the promoters of defence genes during plant immune response [8]. However, in our study, when RAD51 was over-expressed, it did not modulate IFN-α induced ISRE activity (in contrast with BRCA2 expression) ( Figure 5b).…”
Section: Discussionmentioning
confidence: 49%
“…BRCA2 forms a complex with Smad3 and synergizes in regulating the transcription of Smad3-dependent luciferase reporters [7]. In Arabidopsis, BRCA2 is a major regulator of immune gene transcription [8]. In human cells, the expression of two innate immunity genes (UCRP and UBE2L6) were down-regulated after BRCA2 knock down [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, SNI1 (Suppressor of NPR1, Inducible) was proposed to mediate defence gene expression via histone modification 44 . Interestingly, several ssn mutants encode mutated versions of well-established DNA R/R proteins, such as RAD51D (SSN1), SWI/SNF (SSN2) and BRCA2A (SSN3) 30,45,46 . Mutations in any of the three SSN genes results in altered induction of pathogen-responsive genes and increased susceptibility/sensitivity to pathogens and DNAdamaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…7 Since ROS production is associated with the formation of necrotic lesions, it is possible that the increase in HRF in distal tissue is due to ROS signaling or ROS-induced signaling through MeJA, MeSA or other volatile molecules. The link between salicylic acid signaling and homologous recombination is well established, 8 although it is not clear whether it has any direct biological significance. It is possible that the upregulation of PR1 expression in bystander plants is a consequence of shared signaling pathways in response to abiotic and biotic stresses.…”
mentioning
confidence: 99%